Pemanfaatan Laboratorium Agama Untuk Meningkatkan Efektifitas Pada Pembelajaran Pendidikan Agama Islam Kelas Xi Di Sma Negeri 3 Sukoharjo Tahun Pelajaran 2015/2016 - Arifin, Yusuf, Drs. Najmuddin Zuhdi, M.Ag (2016)
Learning Islamic religious education (PAI) is currently just focus on material alone (cognitive). Learning material that requires the practice can not be done in the classroom, because it takes a long time to prepare. Thus, the role of learning media is one of important element to improve the effectiveness of learning. The use of religious laboratory helps students understand and master the materials relating to the practice of worship (fiqh). To realize an efficient and funny teaching learning activities, teachers should have the skills in presenting the materials, conditioning classes, the use of learning media and effective teaching learning process assisted by the use of religious laboratory. This study examines: the use of religious laboratory to improve the effectiveness of the learning of Islamic religious education at XI grade of SMA Negeri 3 Sukoharjo 2015/2016 Academic Year. With the formulation of the problems (1) How are the utilization of religious laboratory in SMA Negeri 3 Sukoharjo 2015/2016 academic year. (2) How are the effectiveness of the utilization of religious laboratory in learning Islamic religious education at XI grade of SMA Negeri 3 Sukoharjo 2015/2016 Academic Year. The objectives of the research (1) to describes the utilization of relious laboratory at SMA Negeri 3 SKH 2015/2016 academic year (2) To describes the effectiveness of utilization of religious laboratory in learning Islamic religious education at XI grade of SMA Negeri 3 Sukoharjo 2015/2016 Academic Year. This research is a field research with a qualitative approach means that this research requires the writer to enter directly into the field of study, then interact directly to obtain valid and accurate data as needed. This data collection techniques using interviews, observation, and documentation. the technique of analyzing data is using descriptive qualitative inductive method, that is the pattern of reasoning starts with using statements which have a distinctive scope and limited in formulating arguments and ending with the general conclusion. The results of this research shows that the utilization of religious laboratory (1) as a medium of learning is also functioned as a place of discussion and meetings Rohis (Islamic Spirituality), (2) Utilization of religious laboratory in studying Islamic religious education (PAI) helps students easily in increasing mastery and understanding of the materials PAI especially in the aspect of fiqh, organizing the material becomes increasingly attractive. Beside that, the utilization of religious laboratory is also used as outing class media that is replacing the atmosphere of learning from saturation, such as learning in classroom atmosphere and make enthusiastic of the students in learning becomes high, (3) Utilization of religious laboratory can improve the effectiveness of learning Islamic religious education at XI grade of SMA Negeri 3 Sukoharjo.